THE INFLUENCE OF PROPHETIC LEADERSHIP ON EMPLOYEE'S ORGANIZATIONAL BEHAVIOR AT SMK-IT AL-KASYAF - Muhamad Alwi Mujahid; Mulyawan Safwandy Nugraha (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
West Java, one of the provinces in Indonesia, with Sundanese nuances that are thick with Islamic law, will affect the psychology of the people. This also affects the vision and mission of organizations and organizational management that prioritizes Islamic values, such as at SMK-IT Al-Kasyaf Sukabumi. Leaders need to understand the things that make employees have a positive perception of the organization. In this case, prophetic leadership as a perfect form of leadership for Muslims because it refers to the characteristics of the prophet. This study aims to determine the relationship between prophetic leadership and organizational culture with organizational commitment in SMK-IT Al-Kasyaf employees. This study used a questionnaire consisting of a prophetic leadership scale compiled by Budiharto, S and Himam, F. (2006), an organizational culture scale and an organizational commitment scale, then analyzed statistically to discuss employee organizational commitment at SMK-IT Al-Kasyaf. The results obtained show that there is a relationship between prophetic leadership and organizational culture with organizational commitment to SMK-IT Al-Kasyaf employees with prophetic leadership and organizational culture contributing 64.6% to the organizational commitment of SMK-IT Al-Kasyaf employees. The content of the abstract, between 150-200 words, just one paragraph. Apparently, for the sake of simplicity, use the same language you use in your writing. Use the Abstract Fill style for this format. If you use this template correctly, all numbering will be generated automatically. So you don't need to edit it manually. Of course, if you create a section of this paper that requires numbering after this template, that number will be followed by the existing section number. Again you don't need to edit the part numbers, because if the contents of this template are deleted, the numbers will be sorted automatically. If you want to try deleting the contents of this template, please backup it first.